Alignment of the CMS tracker with LHC and cosmic ray data - Chatrchyan, S. (2014)
The central component of the CMS detector is the largest silicon tracker ever built. The precise alignment of this complex device is a formidable challenge, and only achievable with a significant extension of the technologies routinely used for tracking detectors in the past. This article describes the full-scale alignment procedure as it is used during LHC operations. Among the specific features of the method are the simultaneous determination of up to 200 000 alignment parameters with tracks, the measurement of individual sensor curvature parameters, the control of systematic misalignment effects, and the implementation of the whole procedure in a multiprocessor environment for high execution speed. Overall, the achieved statistical accuracy on the module alignment is found to be significantly better than 10 mu m.